Inside Front Cover. Issue 7 (5th July 2021) - Connolly, Peter W. R.; Valli, Jessica; Shah, Yash D.; Altmann, Yoann; Grant, James; Accarino, Claudio; Rickman, Colin; Cumming, David R. S.; Buller, Gerald S.
Abstract: Multispectral fluorescence imaging is performed under the laser illumination of multiple wavelengths simultaneously. A plasmonic metasurface is designed to perform colour filtering, composed of an arrangement of circular and elliptical nanoholes etched into an aluminium thin film. The resultant mosaic colour filter array is flip‐chip bonded onto a single‐photon avalanche diode (SPAD) array. High fidelity, full‐colour fluorescence images are reconstructed from as few as three photons per pixel from a variety of biological samples. Further details can be found in the article by P.W.R. Connolly, J. Valli, Y.D. Shah, Y. Altmann, J. Grant, C. Accarino, C. Rickman, D.R.S. Cumming, and G.S. Buller (e202000505 ) Abstract : Multispectral fluorescence imaging is performed under the laser illumination of multiple wavelengths simultaneously. A plasmonic metasurface is designed to perform colour filtering, composed of an arrangement of circular and elliptical nanoholes etched into an aluminium thin film. The resultant mosaic colour filter array is flip‐chip bonded onto a single‐photon avalanche diode (SPAD) array. High fidelity, full‐colour fluorescence images are reconstructed from as few as three photons per pixel from a variety of biological samples. Further details can be found in the article by P.W.R. Connolly, J. Valli, Y.D. Shah, Y. Altmann, J. Grant, C. Accarino, C. Rickman, D.R.S. Cumming, and G.S. Buller (e202000505 )